A Synopsis of the Scolytine Ambrosia Beetles of Thailand (Coleoptera: Curculionidae: Scolytinae) - Beaver, R. A.; Sittichaya, W.; Liu, L-Y. (Zootaxa, 2014)
The present state of knowledge of the scolytine ambrosia beetles of Thailand is summarised to provide a basis for future studies of the fauna and its economic importance in forestry, timber production and crop tree plantations. A checklist of the fauna is provided with information on local and world distribution, host trees, biology and taxonomy. Six faunal elements based on geographical distribution, and the host tree and altitudinal preferences of species are discussed. One hundred and sixty-one species are recorded from Thailand, 67 of them for the first time. The following new synonym is proposed: Euwallacea wallacei (Blandford) (= Xyleborus barbatomorphus Schedl n.syn.). The following new combinations are given: Ambrosiophilus cristatulus (Schedl), Ambrosiophilus latisulcatus (Eggers), Beaverium dihingensis (Eggers), Beaverium lantanae (Eggers) and Immanus desectus (Eggers) are transferred from their present position in Ambrosiodmus; Ancipitis depressus (Eggers) and Ancipitis punctatissimus (Eichhoff) are transferred from Leptoxyleborus; Cyclorhipidion armipenne (Schedl), Cyclorhipidion inarmatum (Eggers), Euwallacea semiermis (Schedl), Fortiborus macropterus (Schedl), Microperus nudibrevis (Schedl) and Wallacellus minutus (Blandford) are transferred from Xyleborus.